Developments of PC based controller for buck converter driven DC motor - Nursyuhada Ashikin, Nor Izlanin (2010)
Switched Mode Power Supplies (SMPS) is the technique proposed in this investigation to control the speed of DC motor. In the design of these power supplies, the semiconductor devices are either switched on or off. It is highly efficient because of the low voltage drop across the semiconductor device when it is on and cause the power consumption is low. The power supply is consists of rectifier and Buck converter. The implementation the PWM Chopper with a MOSFET also needed because nowadays, the chopper switch is obviously a fast power MOSFET with very short switching times and low resistance that reduce the conductive losses but produce extremely high voltage- and current-rates. As the result, PWM signal is used to control the speed of the motor and the output voltage of the buck converter with the adding of PC interface in order to make it easy and friendly user system.